Otorhinolaryngological manifestations in Down syndrome: MERF experience - Anto, Ronald; Natarajan, Kiran; Sampathkumar, Raghunandhan; Kumar, Anand; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Syndromic children often pose a spectrum of challenges to the paediatric otolaryngologist. Syndromes like the Down syndrome present with a multitude of manifestations in the head and neck region and require careful management. Methods: A retrospective study of thirty patients with Down syndrome presenting from January 2013 to January 2018 in a tertiary care setting was done. All patients were evaluated by ENT examination and further investigations based on the complaints. The aim was to study the various ENT disorders in Down syndrome patients and their management. Results: The most common disorder was hearing loss in eleven patients followed by rhinosinusitis in ten patients, adenoid hypertrophy and otitis media with effusion (OME) in six patients and obstructive sleep apnea in three patients. Most of the patients had medical management; very few needed surgery. Successful outcomes were possible for all patients. Conclusions: Dealing with otorhinolaryngological disorders may pose a management challenge in Down syndrome and this requires a well experienced ENT, medical and rehabilitative team to provide optimal management and good quality of life to these children.